Franchising in Singapore : a case study of Bee Cheng Hiang. - Mok, Wynne Pei Chee. (2008)
The scope of our project encompasses the different aspects of franchising; information of which is derived mainly from our literature review on the books, journals, magazines and other research projects related to the subject. First of all, we provide the background information on franchising- its origins and the different definitions and types of franchising available- after which we discuss the advantages and disadvantages.